2017
DOI: 10.1021/acsomega.6b00401
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Synthesis of Deuterosilanes by Direct H/D Exchange Mediated by Easily Accessible Pt(0) Complexes

Abstract: Easily accessible, simple phosphino-platinum(0) complexes catalyze (0.1–1 mol % equivalent) the deuteration of silanes in good yields under mild conditions (60 °C, 1 atm). The catalysis is mediated by platinum(II) deuteride/hydride complexes that are in equilibrium with the precursor Pt(0) complexes. The Pt(II) complexes can also be inserted into the Si–H bond of silanes to give intermediate Pt(IV) complexes. The proposed mechanism for catalysis is supported by density functional theory calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…To achieve our goal of selectively installing four deuterium atoms across an alkyne, we hypothesized that using ethanol–OD or 2-propanol–OD and Si–D would permit deuterium installation in a mild manner. Inspired by previously reported work, we were able to develop a scalable and reliable protocol to make the Si–D on a 94 mmol scale (eq ): For deuterated small molecules to be used as internal standards for quantitative bioanalytical liquid chromatography/mass spectrometry assays, it is typical that at least three to four deuterium atoms are contained in the molecule to allow for sufficient separation of peaks in the mass spectrum. , For terminal alkynes, we proceeded to exchange the acetylenic hydrogen atom for a deuterium atom prior to transfer deuteration . This permitted the synthesis of substrates with five deuterium atoms.…”
mentioning
confidence: 99%
“…To achieve our goal of selectively installing four deuterium atoms across an alkyne, we hypothesized that using ethanol–OD or 2-propanol–OD and Si–D would permit deuterium installation in a mild manner. Inspired by previously reported work, we were able to develop a scalable and reliable protocol to make the Si–D on a 94 mmol scale (eq ): For deuterated small molecules to be used as internal standards for quantitative bioanalytical liquid chromatography/mass spectrometry assays, it is typical that at least three to four deuterium atoms are contained in the molecule to allow for sufficient separation of peaks in the mass spectrum. , For terminal alkynes, we proceeded to exchange the acetylenic hydrogen atom for a deuterium atom prior to transfer deuteration . This permitted the synthesis of substrates with five deuterium atoms.…”
mentioning
confidence: 99%
“…Complex 6 can be obtained instantaneously in quantitative yield by reacting a hexane solution of 4 with 2 molar equivalents of (tBu 2 MeSi) 2 Hg and 1 atm of H 2 at room temperature (Scheme , path a). We have previously demonstrated that reactions of phosphino Pt 0 complexes and H 2 yield platinum hydride intermediates, which react with (tBu 2 MeSi) 2 Hg to yield 6 . Interestingly, when the smaller (tBuMe 2 Si) 2 Hg species was used, a novel hexacoordinated Pt IV complex A , which has four silylmercury substituents, was obtained (Scheme , path b; see the Supporting Information for details).…”
Section: Methodsmentioning
confidence: 99%
“…9,10b Catalysts for the deuteration of silanes (b) include ruthenium-polyhydrides, 13 half-sandwich rhodium(III) derivatives, 14 iridium(III)-NHC compounds, 15 and platinum(0)-phosphine species. 16 To our knowledge, catalysts for the reactions with germanes (c) and stannanes (d) have not been reported to date. This specificity forces us to prepare or to buy a particular catalyst for the preparation of each class of deuterated reagent that is desired.…”
mentioning
confidence: 99%
“…Some complexes of iron, cobalt, rhodium, and iridium stabilized by P,N,P- and N,N,N-pincer and chelate-diphosphines and NHC ligands have shown to be efficient for the exchange in boranes (a). Deuterated pinacolborane (pinBD) has been also synthesized in high yield, by deuterogenolysis of B 2 pin 2 , in the presence of iron and cobalt precursors. , Catalysts for the deuteration of silanes (b) include ruthenium-polyhydrides, half-sandwich rhodium­(III) derivatives, iridium­(III)-NHC compounds, and platinum(0)-phosphine species . To our knowledge, catalysts for the reactions with germanes (c) and stannanes (d) have not been reported to date.…”
mentioning
confidence: 99%